KINERJA LINGKUNGAN DAN PROFITABILITAS TERHADAP CARBON EMISSION DISCLOSURE PADA PERUSAHAAN CONSUMER NON CYCLICALS - Maryono, Agus; Ermawati, Yuli (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2024)
The issue of environmental change is currently a hot topic throughout the word. The biggest cause of global warming is industrial activities which are increasingly developing and also producing large amounts of emissions. Therefor, disclosing carbon emissions is a form of corporate social and moral responsibility toword society to reduce carbon emissions. This research is entitled The Influence of Environmental Performance and Profitability on Carbon Emission Disclosure in Non Cyclical Consumer Companies Listed on the Indonesia Stock Exchange in 2021 – 2022. This research aims to test and analizy the influence of environmental performance and profitability on carbon emission disclosure. This sample in this research is secondary data from non cyclicals consumer companies listed on the Indonesia Stock Exchange (BEI). The sampling techique used purposive sampling with a total sample obtained 18 companies with observations for 2 years. Current environmental performance and profitability have a significant impact on CO2 emission disclosure. this is because companies that are major consumer with strong environmental dan profitability tend to be better at disclosing their carbon emissions to gain investor trust